Role of Analysis CVP (Cost-Volume-Profit) as Important Indicator for Planning and Making Decisions in the Business Environment - Lulaj, Enkeleda; Iseni, Etem (European Journal of Economics and Business Studies, 2018)
This research intends to know how much the Cost-Volume-Profit Analysis is used to planning and making decisions in the business environment. The research has been done in manufacturing and service enterprises, using the combination of econometric models in order for the research to be as accurate and to have positive effect. The data are realized through structured questionnaires, using the Mann-Whitney U test, Brunner Munzel test, p-value, BootStrap, DF-degree of freedom, percent confidence interval, with the dependent and independent variables etc. In whom case the hypotheses are verified, which are raised .The results of this research showed that amount of product produced has positive effect on sales value to service companies and raising profit to the manufacturing business environment, also exists an important relationship between production and sales, and CVP analysis contributes to growth profitability and break-even in the business environment . So, as conclusion based on the results found from research, cost-volume-profit analysis should be used for making decisions, because the risk threshold evidently decreases by doing such analysis. The great demand from service companies for products it significantly increases profit and producing to manufacturing enterprises.
Keywords: CVP analysis, break even, costs, production, decision making, margin of contribution, risk threshold etc.